Physiological and psychological changes at the end of the soccer season in elite female athletes - Morales, J.; Roman, V.; Yánez, A.; Solana-Tramunt, M.; Alamo, J.; Figuls, A. (Journal of Human Kinetics, 2019)
This study compares and describes relationships among stress-recovery indices, the heart rate variability index, and the Cooper and Yo-Yo IR1 tests among female soccer players during the last six weeks of the competitive season. Sixteen female soccer players engaged in a pre-test of all of the variables. After having their training monitored for six weeks, a post-test was administered. The results revealed significant (p < 0.05) differences in the specific stress-recovery scales of the RESTQ-sport and in the frequency-domain variables of the HRV, although there were no significant differences in the general stress or general recovery scales. The Yo-Yo IR1 test, the Cooper test scores, and the means of the time-domain HRV variables did not exhibit any significant differences between the pre- and the post-test. The RMSSD variations exhibited very large and large correlations with the performance test and the RESTQ-sport variables, respectively. The variations in the HRV frequency-domain variables exhibited significant moderate and large correlations among the variations of the RESTQ-sport scales. Monitoring athletes at the end of the season may reveal contradictions between some variables. To help with the interpretation of these scales, some external aspects, such as athlete strain and monotony of training, should be considered. Keywords: RESTQ-sport; HRV; Yo-Yo IR1; Cooper test; monotony